A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India - Trivedi, Jigneshkumar N.; Campos, Ernesto; Vachhrajani, Kauresh D. (Zootaxa, 2018)
A new species of pinnotherid crab, Arcotheres shahi n. sp., is described on the basis of specimens collected during a crustacean survey along the coastal areas of Pamban fishing harbor in the Gulf of Mannar, Tamil Nadu state, east coast of India. The new species resembles A. pernicola (Bürger, 1895), A. winckworthi (Gordon, 1936) and A. rayi Ahyong & Ng, 2007, in having the dactyli of the longer fourth pereopod longer than that of fifth pereopod. Arcotheres shahi n. sp. differs from these three known species in the shape of female carapace, frontal region and chela, setal pattern on the dactyli of the fourth and fifth pereopods and relative length of the ambulatory pereiopods.